2020
DOI: 10.1002/cam4.3117
|View full text |Cite
|
Sign up to set email alerts
|

The role of surgical intervention for isolated breast cancer liver metastasis: Results of case‐control study with comparison to medical treatment

Abstract: BackgroundCombined with systemic therapy, the surgical intervention for breast cancer liver metastases (BCLM) is increasingly accepted but lacks convincing evidence. The aim of this study was to evaluate the disease control efficacy of hepatic surgery in isolated BCLM patients.MethodsBetween 2012 and 2017, metastatic breast cancer patients with isolated liver metastasis and regular follow‐up were identified. Cohort design was conducted to compare the progression‐free survival (PFS) between the surgical and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…13 Two case matched studies have demonstrated improved survival for patients undergoing liver resection with systemic treatment versus systemic treatment alone, although another case control study has shown no difference in progression free survival between those undergoing surgery and those receiving systemic treatment only. [29][30][31] It seems plausible that a select cohort of patients will achieve a survival benefit from undergoing liver resection for BCLM and a recent meta-analysis has demonstrated a survival advantage for patients undergoing surgery combined with systemic therapy versus those receiving systemic therapy alone. 32 Several other reviews have produced conflicting reports about the evidence of hepatic resection for BCLM.…”
Section: Discussionmentioning
confidence: 99%
“…13 Two case matched studies have demonstrated improved survival for patients undergoing liver resection with systemic treatment versus systemic treatment alone, although another case control study has shown no difference in progression free survival between those undergoing surgery and those receiving systemic treatment only. [29][30][31] It seems plausible that a select cohort of patients will achieve a survival benefit from undergoing liver resection for BCLM and a recent meta-analysis has demonstrated a survival advantage for patients undergoing surgery combined with systemic therapy versus those receiving systemic therapy alone. 32 Several other reviews have produced conflicting reports about the evidence of hepatic resection for BCLM.…”
Section: Discussionmentioning
confidence: 99%
“…In the manuscript, Grazi shows no definitive proof of liver resections (LR) effectiveness for BCLM. However, the author suggests surgery may be possible in selected patients ( 1 - 3 ). Several retrospective case series have been published evaluating patients’ survival following resection for BCLM, reporting results for 5-year overall and disease-free survivals.…”
mentioning
confidence: 99%
“…In the article, those criteria have been identified in radical surgery (margins R0) and saving at least 30% of the liver parenchyma that are general rules of thumb for LR in oncological diseases ( 1 ). Also, the stable skeletal disease could not be a contraindication to resection ( 1 , 4 ), and the only identified prognostic criterion is the interval treatment in metachronous hepatic disease (>24 months) ( 1 , 3 , 4 ). Some considerations in a complex and systemic disease such as BC should be made when treating this patient subgroup.…”
mentioning
confidence: 99%
See 2 more Smart Citations